Why we cannot cancel physically active play - Foster, E. (2020)
As we find ourselves at this time in the world where a pandemic has changed the intricate details of our lives, we are forced to focus on the essentials of life. ... Though we must fulfill our physiological and safety needs to stay alive (i.e., the essentials), if we neglect or cannot fulfill other human needs (e.g., social, intellectual, emotional, self-fulfillment), are we whole? ... Because the author is a physical educator, her mind has been drawn to the impact the pesky COVID-19 pandemic is having on physical activity (PA) and sport. ... For athletes, the devastation is insurmountable. Effects of detraining can be mental strain, potential for getting sick, depression and anxiety which can cause lack of motivation for doing normal daily activities, loss of interest in pleasurable engagements, tiredness, and unexplained physical problems .... Further insufficient exercise may increase the risk of catching the feared virus. Thats why physical ctivities during the lockdown are necessary.